Impact of COVID-19 on Attitudes to Climate Change and Support for Climate Policies - Mohommad, Adil.; Pugacheva, Evgenia (Washington, D.C. : International Monetary Fund, 2022)
This paper inquires into how individual attitudes to climate issues and support for climate policies have evolved in the context of the pandemic. Using data from a unique survey of 14,500 individuals across 16 major economies, this study shows that the experience of the COVID-19 pandemic increased concern for climate change and public support for green recovery policies. This suggests that the global health crisis has opened up more space for policy makers in key large economies to implement bolder climate policies. The study also finds that support for climate policies decreases when a person has experienced income and/or job loss during the pandemic. Protecting incomes and livelihoods in the near-term is thus important also from a climate policy perspective.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Climate Change, Climate Policy and COVID-19; Climate Policies Decrease; Climate Policy Perspective; Climate; Global Warming; Natural Disasters and Their Management